2016
DOI: 10.19082/2542
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Effect of Ultra High Frequency Mobile Phone Radiation on Human Health

Abstract: IntroductionPublic and occupational exposure to electromagnetic fields due to the growing trend of electronic devices may cause adverse effects on human health. This paper describes the risk of mutation and sexual trauma and infertility in masculine sexual cell by mobile phone radiations.MethodsIn this study, we measured the emitted dose from a radiofrequency device, such as switching high voltage at different frequencies using a scintillation detector. The switching high voltage power supply (HVPS) was built … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 9 publications
0
17
0
1
Order By: Relevance
“…The temperature increased between ranges of 0.2˚C -0.6˚C can caused micro thermal effect in cellular and subcellular levels. The results of this study and International Commission of Non-ionization Radiation Protection (ICNIRP) reports showed the people who spend more than 50 minutes a day using a cell phone could have early dementia or other thermal damage due to the burning of glucose in the brain[13].…”
mentioning
confidence: 79%
“…The temperature increased between ranges of 0.2˚C -0.6˚C can caused micro thermal effect in cellular and subcellular levels. The results of this study and International Commission of Non-ionization Radiation Protection (ICNIRP) reports showed the people who spend more than 50 minutes a day using a cell phone could have early dementia or other thermal damage due to the burning of glucose in the brain[13].…”
mentioning
confidence: 79%
“…The investigation of the radiation has been extended to all Biosystems Rifai and Hakami discussed even up to the cellular level and various diseases associated with the electromagnetic radiation due to absorptions. Moradi et al experimented exposure due to Ultra low‐frequency and concluded usage of the mobile phone could cause early dementia or other thermal damage. Heynick surveyed on an experimental finding of cancer studies related to radiation.…”
Section: Motivations and Problem Statementmentioning
confidence: 99%
“…‐ Therefore, there is an urgent need for suitable protective materials which can shield devices and living organisms. Recent references also highlight the issues concerning EMI especially in the healthcare sector ,…”
Section: Introductionmentioning
confidence: 99%